The effect of disocclusion time-reduction therapy to treat chronic myofascial pain: A single group interventional study with 3 year follow-up of 100 cases - Prafulla Thumati; Roshan P Thumati (Wolters Kluwer Medknow Publications, 2016)
Purpose: The purpose of this study is to evaluate the longevity of reduced disclusion time in treating and removing myofascial pain dysfunction symptoms following the T-Scan-based, immediate complete anterior guidance development (ICAGD) coronoplasty. This measured occlusal adjustment has been shown to reduce the muscle hyperactivity of myofascial pain. Methods: Myofascial pain symptomatic patients were recruited as per the diagnostic criteria for temporomandibular disorders (TMDs), including the clinical protocol and assessment instruments outlined by the international RDC/TMD consortium network (version: January 20, 2014) to assess the efficacy of reduced disclusion time in left and right lateral excursions to resolve the myofascial pain symptoms. As per the inclusion and exclusion criteria, 100 cases were treated with ICAGD in three visits, each 1 week apart. Recall disclusion time measurements were recorded every 3 months over 3 years. The RDC/TMD questionnaire was used for symptom assessment at every recall visit. ICAGD brought pretreatment prolonged disclusion time down to <0.4 s, as quantified from T-Scan force and time data records, while the subjects were assessed for symptom relief. The Wilcoxon signed-rank test was used for statistical analysis (P < 0.05). Results: Changes in the intensity of many symptoms from reducing the disclusion time to <0.4 s were statistically significant from treatment day 1, and onward through the 3-year period of observation (P < 0.05). Conclusion: The results indicate that ICAGD reduces the musculoskeletal symptoms of myofascial pain, such that this methodology increases clinical therapeutic success.